Effect of Different Culture Containers to Cell Densities of Nitzschia in Laboratory Scale - Mohammad Faizal Ulkhaq; Yeni Dwi Kharismawati; Arif Habib Fasya (Airlangga University, 2019)
The study aimed to determine the type of culture container for increasing the cell density of Nitzschia and producing the hightly cell biomass. The stages of this study were sterilization of containers and media, making diatom fertilizers and agar media, culture of Nitzschia in agar medium, culture of Nitzschia in test tube, and culture of Nitzschia in glass and plastic containers. The result showed that the cell density of Nitzschia cultured in the glass container was higher than plastic containers. Further study was needed to determine the nutrient composition of Nitzschia that culture in glass containers.Keyword : Nitzschia culture, Laboratory scale, Glass, Plastic container.